Eleocharis equisetina C. Presl (Cyperaceae): An Extended Distribution to the Andaman and Nicobar Islands and Notes on its Identity - Chandore, A. N.; Auti, S. G.; Gosavi, K. V. C.; Shendage, S. M.; Kamble, M. Y. (Indian Forester, 2020)
No Abstract.